AFIKS PEMBENTUK VERBA DALAM BAHASA PAMONA - TO’UMBO, YENI MARGARETHA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT The focus of this research problem is (1) what affixes can form verbs in Pamona language ?, (2) what is the function and meaning of verb-form affix in Pamona language ?. The purpose of this research are: (1) to describe verbal forming affixes in Pamona language, (2) to identify the function and meaning of verbal-form affix in Pamona language. This research uses the method of referring, with tapping technique and technique of luctive conversation. Further analyzed and presented using referential method, and in data analysis used formal and informal method. The verbal-forming affix in Pamona is (1) the prefix maN-, moN-, me, na-, mombe-, mampo-, mampaka-, te- , -i with the group, -waka with the group, maN - / - ka, na - / - ka, and -um-. Keywords: affix, verbs, Pamona language.